The Images and Data Bases Group at University of São Paulo - Traina, Agma Juci Machado; Traina Júnior, Caetano; Ciferri, Cristina Dutra Aguiar; Sousa, Elaine Parros Machado de; Rodrigues Júnior, José Fernando; Cordeiro, Robson Leonardo (Journal of Information and Data Management, 2013)
reated in the middle of the 1990s, the Images and Data Bases Group (Grupo de Bases de Dados e de Imagens) at the Institute of Mathematics and Computer Science of the University of São Paulo at São Carlos – GBdI-ICMC-USP – has since the start worked in the development of core databases and data analysis techniques to handle large databases for scientific applications involving complex data. Its research activities include applying Fractal Theory concepts to improve analysis and search operations over very large datasets, development of search algorithms, indexing structures and optimization techniques for similarity-based queries, development of data mining and data warehousing techniques aimed at dealing with datasets with large cardinality and dimensionality, information visualization for data stored in relational databases and techniques to allow data integration from diverse sources including those maintained in complex structures. Derived from those basic research activities, the research group has generated several tools released for the community in general, including tools for computer-assisted medical diagnosis and for climate change analysis, libraries to help the development of efficient and efficacious biological applications, and software libraries to help including similarity queries into existing DBMS.